Communicating Sustainability in Communicative City: Problems on Implementing SDGS in Indonesia - Noviansyah, Alvin; Sutriadi, Ridwan (European Publisher, 2019)
Sustainable Development Goals has been implementing in one way or another across the globe, especially in developing country like Indonesia. Although it has been around since 2016, its implementation is still stalling. The problems with the goals are not the main idea or why do we have to adopt it. Communicating goals is the first problem. This problem arises because of differences in understanding regarding the SDGs and the role of the agreement in development. The communicative city may emerge as an option offered to resolve the problem. This paper aims to illustrate why Communicative City Approach might be the tools needed to achieve the Sustainable Development Goals, while also aim to explore what is important to focus on in implementing the approach. Method use focuses on a qualitative method while emphasizing on literature review, especially analysing SDGs reports published by organizations about the implementation of SDGs for the last years. Key findings are that SDGs also has its effort to localize the Goals and Targets as on to make it easier for the government to achieve the goals needed, although the effort may be further advanced by utilizing the communicative approach, especially considering the communicative principles in socializing SDGs to local level government. This research concludes that although on more empirical levels, the communicative approach may improve significance on our effort to achieve the Sustainable Development Goals.